2004
DOI: 10.1002/app.21272
|View full text |Cite
|
Sign up to set email alerts
|

The effects of chemical structure and synthesis method on photodegradation of polypropylene

Abstract: ABSTRACT:The effects of chemical structure and synthesis method on the photodegradation behavior of polypropylene (PP) were investigated in injection-molded samples exposed to ultraviolet radiation (UV) at 60°C. For this purpose, three PP samples with different chemical structures were chosen: two homopolymerized PP samples (H 1 P, synthesized by bulk polymerization; whereas H 2 P was synthesized by Ziegler-Natta catalyst) and copolymerized PP sample (CP). The photodegradation was characterized by melt flow ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 20 publications
2
24
0
1
Order By: Relevance
“…It was found that photo-oxidation only leads to slight changes in the DSC thermogram of pure PP. The DSC curve shape is qualitatively not modified, however it is slightly shifted towards lower temperatures [37,[57][58][59][60]. In consequence, the melting temperature and the maximum lamellar thickness of pure PP tend to slightly decrease during photo-oxidation (Table 1).…”
Section: Morphological Changesmentioning
confidence: 95%
See 2 more Smart Citations
“…It was found that photo-oxidation only leads to slight changes in the DSC thermogram of pure PP. The DSC curve shape is qualitatively not modified, however it is slightly shifted towards lower temperatures [37,[57][58][59][60]. In consequence, the melting temperature and the maximum lamellar thickness of pure PP tend to slightly decrease during photo-oxidation (Table 1).…”
Section: Morphological Changesmentioning
confidence: 95%
“…Furthermore, a slight increase of the original crystalline content is also observed for pure PP during exposure to UV radiation (Table 1). It is well evidenced that the crystalline content of polypropylene increases at the beginning of oxidation [35][36][37]57,59,60,[63][64][65]. This phenomenon has been explained as due to chain scission, which initially is the major driving force of the oxidative process, and leads to increasing segment mobility and chain arrangements, favouring further crystallisation [58].…”
Section: Morphological Changesmentioning
confidence: 97%
See 1 more Smart Citation
“…Devido ao alto número de cisão de cadeias, o valor do MFI das amostras expostas natural e artificialmente aumentou bastante, chegando a valores que não puderam ser medidos, uma vez que o fluxo da massa polimérica pela matriz era muito rápido e descontínuo. De acordo com vários autores 1,34,35 , este tipo de comportamento é conseqüência do mecanismo de degradação do PP, que envolve reações de quebra de cadeias, que ocorrem através da cisão β de radicais alcoxi (PPO•) gerados pela auto-oxidação do PP (reação 3 do Esquema 1) ou pela foto-clivagem de hidroperóxidos (reação 5). Como subproduto dessas reações temse a formação de grupos carbonila, que é o principal grupo quími-co característico da degradação oxidativa do PP.…”
Section: Medidas De íNdice De Fluidez E De Infravermelhounclassified
“…Many of those parts, having been exposed to UV light for long periods of time are heavily photo-oxidized because of the relative high photosensitivity, especially if they were made of PP; hence changes are expected in the thermal behavior, mechanical properties, and surface morphology of the products. [1][2][3][4][5] Photo-degradation of LDPE/PP blend, 6 PC/PP blend, 7 blends of PP with recycled PP 8 has been studied. PP/LDPE blends compatibilized with rubber-PP-graft copolymers or ethylene-propylene-dienemonomer rubber (EPDM) copolymer have been reported more susceptible to be photo-oxidized than incompatible blends.…”
Section: Introductionmentioning
confidence: 99%